Resilience Benchmarking: How Small Hotels Can Ensure Their Survival and Growth during Global Disruptions - Kolodiziev, O.; Dorokhov, O.; Shcherbak, V.; Dorokhova, L.; Ismailov, A.; Figueiredo, R. (MDPI, 2024)
This study aimed to develop a resilient benchmarking system for small hotels in Ukraine, designed to ensure their survival and growth amid global disruptions and local crises. Given the severe challenges associated with the COVID-19 pandemic and military actions, the resilience of the regional tourism business is particularly relevant. The methods used in this study, including factor and cluster analysis, taxonomy, and dendrograms, enabled the development of development programs for two clusters of hotels: those located in areas with increased military risk and those in relatively safe territories. The taxonomic analysis revealed signifcant differences in managerial practices and operational effciency, largely determined by the geographic location of the hotels. Hotels in active combat zones experienced a 40% reduction in tourist fow and fnancial instability, while hotels in safe areas demonstrated a 30% higher level of customer satisfaction. The application of advanced security systems and modern marketing techniques led to a 40% reduction in incidents.
Keywords: resilient benchmarking; small hotels; tourism; regional impact; operational effciency; strategic adaptation